Pytania i odpowiedzi. Uczniowie gimnazjum czytają "Elementarz etyczny" Karola Wojtyły = Questions and answers. Junior high school students read Karol Wojtyla`s "Ethical Primer" - Kobyłecka, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nowadays young people often find themselves lost and unable to distinguish between good and evil. They ask themselves questions about the true sense of existence and about what is most important and precious in human life. They keep looking for authorities likely to become their leaders and masters.
Keywords: Jan Paweł II, papież (1929-2005); etyka chrześcijańska; młodzież gimnazjalna; badania ankietowe